2020
DOI: 10.3892/mmr.2020.11203
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA ANRIL knockdown suppresses apoptosis and pro-inflammatory cytokines while enhancing neurite outgrowth via binding microRNA-125a in a cellular model of Alzheimer's disease

Abstract: The present study aimed to investigate the effect of the long non-coding rna antisense non-coding rna in the inK4 locus (lnc-anril) knockdown on apoptosis, neurite outgrowth and inflammation based on a PC12 cellular alzheimer's disease (ad) model. a cellular ad model was constructed by treating nerve growth factor stimulated PC12 cells with amyloid β (aβ) 1-42 and then control knockdown plasmid and lnc-anril knockdown plasmid were transfected in the Pc12 cellular ad model as the Kd-negative control (nc) group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 35 publications
1
34
0
1
Order By: Relevance
“…The data of the present study were consistent with this previous finding, verifying that ANRIL knockdown could inhibit the occurrence of AR in vitro by downregulating the production of inflammatory cytokines and mucus. Of note, Zhou et al ( 39 ) discovered that silencing ANRIL could sponge miR-125a-5p to inhibit the progression of Alzheimer's disease. However, the findings of the present study revealed that ANRIL could bind to miR-15a-5p in AR.…”
Section: Discussionmentioning
confidence: 99%
“…The data of the present study were consistent with this previous finding, verifying that ANRIL knockdown could inhibit the occurrence of AR in vitro by downregulating the production of inflammatory cytokines and mucus. Of note, Zhou et al ( 39 ) discovered that silencing ANRIL could sponge miR-125a-5p to inhibit the progression of Alzheimer's disease. However, the findings of the present study revealed that ANRIL could bind to miR-15a-5p in AR.…”
Section: Discussionmentioning
confidence: 99%
“…The cells were grown up to 70-90% confluency for experimental purposes [ 16 ]. PC12 cell is an excellent neuronal model for AD in previous studies [ 17 , 18 ]…”
Section: Methodsmentioning
confidence: 99%
“…miR-574-5p mPGES-1 competitively regulates genes related to inflammation and proliferation [169] is increased in the cortex of APP KO mice [171] miR-206 MyoD competitively regulates genes related to differentiation [170] is increased in the brain of an AD mouse model [172] miR-222 CDK4 cooperatively regulates cellular senescence by targeting genes related to the cell cycle [174] is decreased in the serum of AD patients [173] miR-122 BCKDK, ALDOA, NDRG3, CCNG1, CAT1 enhances destabilization of miRNA in the regulation of energy metabolism, stress response and cell cycle [176] is increased in the brain of AD patients [175] FMRP miR-128-3p mGluR5 competitively regulates astroglial development by targeting glutamate receptor genes [179] is increased in monocytes of AD patients [178] miR-181d MAP1B, Calm1 cooperatively regulates axon elongation by targeting genes crucial for calcium signaling [180] is altered in an AD model and in AD patients [181] miR-125b NR2A cooperatively regulates synaptic strength by targeting an NMDA receptor subunit gene [182] is increased in the CSF of AD patients [183] miR-132 p250GAP? cooperatively regulates synaptic strength possibly by targeting genes related to Rho family GTPase [182] is decreased in the exosome of AD patients [184] hnRNP C miR-544 SOCS1 competitively regulates circRNA in inflammation by targeting genes related to cytokine signaling [185] is increased in high LOAD risk SNPs [186] RCAN1 [190] is decreased in the serum of AD patients [192] miR-18b is increased in serum of AD patients [192] miR-351 UVRAG negatively regulates miRNA biogenesis in autophagy by targeting genes related to the autolysosomal pathway [190] is increased in the hippocampus of an AD mouse model [193] miR-125a is increased in AD cellular model [194] PABP miR-2 n.d. facilitates miRISC onto the 3'-UTR of targeting gene [114] n.d.…”
Section: Celf1mentioning
confidence: 99%
“…In addition, EWS is involved in the post-transcriptional gene regulation via miR-125a and miR-351 that results in the deregulation of autophagy inhibition [ 191 ]. Both miR-29b and miR-18b are known to be AD biomarkers [ 192 ], and the expressions of miR-125a and miR-351 are altered in an AD model [ 193 , 194 ]. PABP has a role in promoting the association of miRISC with mRNAs regulated by miR-2, which targets neural genes according to a computational analysis [ 114 ].…”
Section: Interplay Between Rna-binding Proteins and Micrornas In Neurodegenerative Diseasementioning
confidence: 99%